Al-Khath Al-‘Arabi wa Juhud Al-Muslimin fi Al-Muhafazhah ‘Alaihi - Syuhadak, Syuhadak (UIN Maulana Malik Ibrahim Malang, 2016)
لاخفاء إن حسن الخط من أحسن الأوصاف التي يتصف بها الكاتب وأنه يرفع قدره على الناس، ويكون وسيلة لنجاح مقاصده وبلوغ مآربه مع ماينضم الى ذلك من الفوائد التي لاتكاد تحصى كثرة. وقد قال أمير المؤمنين علي كرم الله وجهه: ((الخط الحسن يزيد الحق وضوحا)).الخط العربي سيمة من سيمات حياة إسلامية في دولة فيها مسلمون. فجهود أبناء المسلمين فيها على تعلمه ونشره وحفظه تدل على محبتهم الإسلام. It cannot be denied that the beauty of calligraphy is an excellence correlated to its writer that will raise his/ her ability higher than others. It also become medium for its owner to come to his/ her dreams which contain unlimited benefit. Amirulmukminin, Ali r.a. said a beautiful calligraphy will make the truth is clearer and more understandable. The existence of Islamic calligraphy is an evidence of Islamic religion life in a country. Therefore, effort from Islamic generation to learn, teach, and preserve it, is the manifestation of their affection to Islam.